Inquiry Into Teaching: Using Reflective Teaching to Improve My Practice - Sarah E Pennington (Networks: An Online Journal for Teacher Research, 2015)
How effective is reflective teaching in increasing the engagement and achievement of pre-service teachers when utilized by a first-year college instructor? This article documents a practitioner inquiry project in which I reflected both on my own observations and student feedback regarding what teaching methods were most beneficial in an undergraduate elementary education class. Data included student feedback, personal researcher journal entries, student quiz scores, and format for presenting material in class. Pre-service teacher engagement and learning were both enhanced by integration of videos, activities, and higher level questions into class sessions. The results of this research affirm the power of reflective teaching while also reflecting the need to more actively engage pre-service teachers in this practice.